2017
DOI: 10.1016/j.celrep.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of TARP γ-2 on Glutamate Efficacy Can Account for AMPA Receptor Autoinactivation

Abstract: SummaryFast excitatory transmission in the CNS is mediated mainly by AMPA-type glutamate receptors (AMPARs) associated with transmembrane AMPAR regulatory proteins (TARPs). At the high glutamate concentrations typically seen during synaptic transmission, TARPs slow receptor desensitization and enhance mean channel conductance. However, their influence on channels gated by low glutamate concentrations, as encountered during delayed transmitter clearance or synaptic spillover, is poorly understood. We report her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 78 publications
3
51
0
Order By: Relevance
“…A number of investigations have focused on the structure and mechanism of modulation of AMPA receptors with the TARP stargazin, also known as γ2 (Cho et al, 2007;Tomita et al, 2005;MacLean and Bowie, 2011;MacLean et al, 2014;Cais et al, 2014;Zhang et al, 2014;Carbone and Plested, 2016;Shaikh et al, 2016;Twomey et al, 2016;Zhao et al, 2016;Coombs et al, 2017;Ben-Yaacov et al, 2017;Twomey et al, 2017;Baranovic and Plested, 2018). These studies show that γ2 interacts with the lower lobe of the ligand-binding domain (LBD) and the preM1 linker via an electrostatic patch, which may stabilize closed cleft states of the LBD, enhancing agonist efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigations have focused on the structure and mechanism of modulation of AMPA receptors with the TARP stargazin, also known as γ2 (Cho et al, 2007;Tomita et al, 2005;MacLean and Bowie, 2011;MacLean et al, 2014;Cais et al, 2014;Zhang et al, 2014;Carbone and Plested, 2016;Shaikh et al, 2016;Twomey et al, 2016;Zhao et al, 2016;Coombs et al, 2017;Ben-Yaacov et al, 2017;Twomey et al, 2017;Baranovic and Plested, 2018). These studies show that γ2 interacts with the lower lobe of the ligand-binding domain (LBD) and the preM1 linker via an electrostatic patch, which may stabilize closed cleft states of the LBD, enhancing agonist efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Heterologous expression. We expressed recombinant AMPAR subunits and TARPs (plus EGFP) in HEK293 cells maintained under standard protocols, as described previously 25 . AMPAR subunit cDNAs (rat) were 'flip' splice variants and the GluA2 forms were additionally R/G edited.…”
Section: Methodsmentioning
confidence: 99%
“…We next considered whether the presence of conducting desensitized receptors could account quantitatively for our observations. To examine this, we incorporated such states into a modified version of a kinetic scheme we used previously to describe AMPAR/TARP concentration-dependent behaviors 25 (Scheme 1; Fig. 5a), and attempted to mimic the macroscopic kinetics and NSFA of GluA2(R)/ -2 by varying the rate constants and conductances.…”
Section: Figure 1 Q/r Editing Affects the Kinetics And Variance Of Gmentioning
confidence: 99%
See 1 more Smart Citation
“…Auxiliary subunits can slow AMPA receptor kinetics in heterologous expression (Priel et al, 2005) and reduce their tendency to desensitize whilst boosting activation (Coombs et al, 2017). Evidence for desensitization-resistant AMPA receptors in the brain is so far limited to high-frequency activity at certain connections in the cerebellum (Lu et al, 2017;DiGregorio et al, 2007), where hints of a distinct pharmacology were reported (Devi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%